Pedagogical Personal Characteristics of Professional Employees in Preschool Educational Organizations - Soliyev Ilhomjon Sobirjonovich; Kholmatova Muslimakhon Toirjon kizi (Zien Journals, 2023)
The article analyzes the space of spiritual and moral education in modern education. Analyzing the main approaches to understanding spirituality, the authors reveal the essence of spiritual and moral education, which makes it possible to determine its subject.
Keywords: man; upbringing; spirituality; spiritual and moral education